Implementation of Character Education in Religious Culture: Multi-case study in Public and Islamic Junior High Schools - Yunita Noor Azizah (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2019)
In an effort to internalize religious values in children’s character, a religious culture is needed in the school. This is because the portion of time given to Islamic subjects in schools is only relatively less on a weekly level, so the opportunities for teachers to provide guidance and direction are also relatively small. In addition, the religious values that exist in children are often defeated by the negative cultures around it. Therefore, character education in religious culture is considered to be able to shape the character of the students. This research aims to describe: (1) Character education planning on religious culture at State Junior High School 4 & Madina Islamic Junior High School (2) Implementation of character education on religious culture in State Junior High School 4 & Madina Islamic Junior High School. This research uses a qualitative approach using a multi-case study design. Data collection is conducted using in-depth interviews, observations & documentation. Research informants are principals of school, Islamic education teachers. The data obtained by the informant & the subjects studied were interpreted and analyzed using cross-case data analysis. The findings of the study proved that: (1) Character education planning on religious culture at State and Islamic Junior High School is carried out using the standard set of character of students, forming religious culture, and providing supporting facilities, setting the standard competencies of graduates, and dividing the responsibility of mentor for each student. (2) The implementation of character education in religious culture in State Junior High School 4 is carried out using integrating the standard characters contained into the daily, weekly, monthly religious culture. And the application of character education in religious culture at Madina Islamic Junior High School is done using integrating the raw characters contained into the religious culture.